(3fRgI GdWQa aj Yde GdUQas - (3GdejOGfj , CHh GdaVd CMeO Hf eMeO Hf CMeO Hf EHQGgje GdejOGfj GdfjSGHhQj,J (B518 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi BdGFg hHYO aEf GdJUQja CMO CQcGf GdCOH hHg jYQa SYg cdGe GdYQH s
(3BNQgG (B:s
(3heaYhdkG BNQ hgh GdPi Md GdaYd Hg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B63s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs